Synthesis of Novel Isoxazoline/Isoxzolyl Pyrano Heterocyclic Annulated Flavones - Sydhulua, Rachakonda; Hemasria, Yerrabelly (Asian Journal of Chemistry, 2023)
The synthesis of new isoxazoline/isoxazole pyrano fused flavone derivatives from 6-hydroxy 5-formyl flavone via in situ generation of nitrile oxide from aldoxime using ceric ammonium nitrate (CAN) as an oxidant followed by intramolecular cycloaddition reaction at olefin/alkyne functions is reported in high yields. The reaction involves regio selective annulation at C5/C6 position in preference to the C6/C7 position of flavones. All the synthesized compounds were successfully characterized by IR, 1H NMR, 13C NMR and ESI-MS.